Impact of comprehensive management on clinical outcomes in hypertensive patients with coronary artery disease: HIJ-CREATE sub-study. (25th November 2020) - Ogawa, H; Sekiguchi, H; Jujo, K; Kawada-Watanabe, E; Arashi, H; Yamaguchi, J; Hagiwara, N
Abstract: Background: There are limited data on the effects of blood pressure (BP) control and lipid lowering in secondary prevention of coronary artery disease (CAD) patients. We report a secondary analysis of the effects of BP control and lipid management in participants of the HIJ-CREATE, a prospective randomized trial. Methods: HIJ-CREATE was a multicenter, prospective, randomized, controlled trial that compared the effects of candesartan-based therapy with those of non-ARB-based standard therapy on major adverse cardiac events (MACE; a composite of cardiovascular death, non-fatal myocardial infarction, unstable angina, heart failure, stroke, and other cardiovascular events requiring hospitalization) in 2, 049 hypertensive patients with angiographically documented CAD. In both groups, titration of antihypertensive agents was performed to reach the target BP of <130/85 mmHg. The primary endpoint was the time to first MACE. Incidence of endpoint events in addition to biochemistry tests and office BP was determined during the scheduled 6, 12, 24, 36, 48, and 60-month visits. Achieved systolic BP and LDL-Cholesterol (LDL-C) level were defined as the mean values of these measurements in patients who did not develop MACEs and as the mean values of them prior to MACEs in those who developed MACEs during follow-up. Results: During a median follow-up of 4.2 years (follow-up rate of 99.6%), the primary outcome occurred in 304 patients (30.3%). Among HIJ-CREATE participants, 905 (44.2%) were prescribed statins on enrollment. Kaplan–Meier curves for the primary outcome revealed that there was no relationship between statin therapy and MACEs in hypertensive patients with CAD. The original HIJ-CREATE population was divided into 9 groups based on equal tertiles based on mean achieved BP and LDL-C during follow-up. For the analysis of subgroups, estimates of relative risk and the associated 95% CIs were generated with a Cox proportional-hazards model (Figure 1). The relation between LDL cholesterol level and hazard ratios for MACEs was nonlinear, with a significant increase of MACEs only in the patients with inadequate controlled LDL-C level even in the patients with tightly controlled BP. Conclusions: The results of the post-hoc analysis of the HIJ-CREATE suggest that clinicians should pay careful attention to conduct comprehensive management of lipid lowering even in the contemporary BP lowering for the secondary prevention in hypertensive patients with CAD. Funding Acknowledgement: Type of funding source: None